2022
DOI: 10.4103/jmas.jmas_87_21
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical mapping of the biliary tree during laparoscopic cholecystectomy by using indocyanine green dye

Abstract: Background: Fluorescent cholangiography using intravenous indocyanine green (ICG) is a noninvasive technique that enables real-time intraoperative imaging of biliary anatomy. The objective of this study was to visualise the biliary anatomy in routine and complicated cases of laparoscopic cholecystectomy (LC). Methods: This was a prospective observational study of patients undergoing LC for various indications. After obtaining consent, 5 mg/1 ml of ICG d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other reports experienced lower cystic duct detection rates with acute inflammation while using ICG imaging. Bandari, et al reported lower rates of CBD and cystic duct detection in patients with acute cholecystitis at 80% and 90% respectively compared to 100% visualization in other groups (cholelithiasis, chronic cholecystitis, and mucocele, polyps) ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports experienced lower cystic duct detection rates with acute inflammation while using ICG imaging. Bandari, et al reported lower rates of CBD and cystic duct detection in patients with acute cholecystitis at 80% and 90% respectively compared to 100% visualization in other groups (cholelithiasis, chronic cholecystitis, and mucocele, polyps) ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further prospective large studies are required before standardization of care focusing on the incidence of BDI, time to visualization of biliary anatomy, and outcomes when ICG fails to help identify. A Summary of literature pertaining to the utility of ICG for anatomical mapping is provided in Table 1 ( 24 , 29 32 , 35 , 36 , 39 44 , 46 51 , 56 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the intravenous route, ICG is administered 30 min before the surgery. Since ICG is metabolized by the liver and excreted in bile, the biliary structures are visualized intraoperatively immediately after dissection of the Calot’s triangle[ 51 , 52 ]. For the intrabiliary route, the gallbladder is punctured with cholangiogram or pigtail catheter mid-surgery, and the bile is aspirated and mixed with ICG solution, and then re-injected into the gallbladder[ 45 ].…”
Section: Resultsmentioning
confidence: 99%